The Theological Perspective on Interreligious Tolerance in North Sulawesi, Where the Role of Pastors in Maintaining the Authenticity of Biblical Values - Saliareng, Riandli (PT. Giat Konseling Nusantara, 2024)
This article explores the theological perspective on interreligious tolerance in North Sulawesi, focusing on the role of pastors in maintaining the authenticity of biblical values amidst the challenges of religious pluralism. The research employs a qualitative approach with a descriptive method, utilizing in-depth interviews and direct observation of pastors from the GPdI (Gereja Pantekosta di Indonesia) denomination. The collected data is analyzed thematically to examine the dynamics of pastors’ roles in safeguarding the integrity of Christian doctrine while adapting to a pluralistic social context. The findings reveal that pastors play a dual role as both citizens of the nation and citizens of heaven. They are required to act as wise social mediators, balancing the demands of interreligious tolerance with their commitment to upholding Christian principles. Love as the foundation of theology is shown to be a key guide in the practice of tolerance, despite the risks of doctrinal compromise if tolerance is excessively applied. Pastors in North Sulawesi function not only as educators but also as role models in social life, demonstrating how Christian faith can coexist harmoniously with other religions without losing its doctrinal integrity. This article provides insights that healthy tolerance requires a deep understanding of theology, inclusive leadership strategies, and efforts to maintain a balance between social harmony and the purity of faith.